Multipass Raman gas analyzer for monitoring of atmospheric air composition - Petrov, Dmitry Vitalievich (Optics and Laser Technology)
An improved gas analyzer based on Raman spectroscopy is presented. The device can measure the content of all molecular species of atmospheric air, whose concentration exceeds the sensitivity threshold. To obtain a high signal-to-noise ratio, a multi-pass optical system for scattering excitation was used together with the compression of the analyzed gas sample to a pressure of 20 atm. A technique for deriving concentrations from Raman spectra of atmospheric air based on the contour fit method is described. At the working pressure, a good agreement between the measurements of the daily air concentration of the carbon dioxide (CO2) and methane (CH4), and the data obtained with a high-sensitive CRDS gas analyzer was obtained. The standard deviation of the measured CH4 concentration values was ~ 20 ppb. Estimates are given for the detection limits of the most common gas impurities in air, as well as for the Raman scattering cross sections for formaldehyde (CH2O), benzene (C6H6), and toluene (C7H8) vapor.